PERAN GURU DALAM PEMANFAATAN MEDIA POWER POINT UNTUK MENINGKATKAN INTERAKSI PEMBELAJARAN DI SDN 03 MANCAGAHAR - Ghaitsa Zahira Salsabiella; Risma Nuriyanti; Nabella Alani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of teachers in utilizing PowerPoint media to improve learning interaction at SDN 03 Mancagahar. The research method used is qualitative with a library research approach. Data were obtained from various sources such as books, scientific journals, and relevant articles. Data collection techniques were carried out through content analysis and analyzed descriptively. The results of the study indicate that teachers play an important role as planners, facilitators, motivators, and evaluators in the use of PowerPoint media. The use of this media can improve learning interaction, as shown by students' active participation in asking questions, answering questions, expressing opinions, and engaging in discussions. In addition, PowerPoint has advantages in presenting material in an attractive, systematic, and varied way, which can increase students’ learning interest. However, there are several obstacles in its implementation, such as limited facilities and infrastructure, as well as teachers' ability to manage instructional media. Therefore, the use of PowerPoint media can enhance learning interaction if supported by teachers’ creativity and competence in managing the learning process effectively.